Long-term follow-up of a randomized trial of biliary drainage in perihilar cholangiocarcinoma. Issue 2 (February 2023) - Nooijen, Lynn E.; Franssen, Stijn; Buis, Carlijn I.; Dejong, Cornelis H.C.; den Dulk, Marcel; van Delden, Otto M.; Ijzermans, Jan N.; Groot Koerkamp, Bas; Kazemier, Geert; van Lienden, Krijn; Klümpen, Heinz-Josef; Kuipers, Hendrien; et al.
Abstract: Background and aims: The DRAINAGE trial was a randomized controlled trial comparing preoperative endoscopic (EBD) and percutaneous biliary drainage (PTBD) in patients with potentially resectable, perihilar cholangiocarcinoma (pCCA). The aim of this study was to compare the long-term outcomes. Methods: Patients were randomized in four tertiary referral centers. Follow-up data were available for all included patients. Primary outcome was overall survival (OS). Secondary outcomes were readmissions, and re-interventions not including in-trial interventions. Results: A total of 54 patients were randomized; 27 in both groups. Median follow-up for both groups was 62 months (95% CI 54–70). The median OS was 13 months (95% CI 7.9–18.1) in the EBD and 7 months (95% CI 0.0–17.2) in the PTBD group ( P  = 0.28). Twenty (37%, n = 8 EBD vs n = 12 PTBD, P  = 0.43) of 54 patients were readmitted at least once, mostly due to drainage-related complications (n = 13, 24%). Of note, 14 out of the 54 patients died within the trial. A total of 76 drainage procedures (32 EBD and 44 PTBD) were performed in 28 patients. The median number of stent or drain placements was 2 (2–4) for the EBD group and 2 (1–3) for the PTBD group ( P  = 0.77). Discussion: Although this follow-up study represented a small cohort, no long-term differences in survival, readmissions, and drainage procedures for EBD and PTBD were found, even when comparing the resected and unresected group. However, this study demonstrates the complexity of biliary drainage for patients with potentially resectable pCCA, even in tertiary referral centers. Graphical abstract: Image 1